Considerations on the public funds use based on the performance: Program budgeting - Boboc Ioana (Budgetary Research Review (BRR), 2011)
Performance concept in economics is a characteristic of economic processes arising from the need to save resources that fall within these processes, while carrying out activities specific to every public entity under the highest quality conditions. In recent years, even the most developed economies feel more and more the need to spend public resources efficiently, effectively and economically, as the defining elements of the performance criteria on the use of these resources. Elaboration and implementation of the budget in terms of efficiency, economy and effectiveness is a prerequisite for achieving appropriate economic and financial management of public resources. This is not just a legal obligation but also a necessity in order to achieve a healthy management, with beneficial effects in economic, social and sustainable development. This study aims to capture some defining elements and key points of performance in the use of public funds by program budgets, considering the recent years' developments related to this method of budget substantiation and implementation.
Keywords: H59; H61; 330; program budget; performance; economy; efficiency; effectiveness